1999
DOI: 10.1177/146642409911900306
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking habits among high school boys in a developing country

Abstract: The aim of this cross-sectional study was to determine the habits, practices, attitudes and knowledge about cigarette smoking among high school boys aged 15-19 years in the United Arab Emirates, and to provide a basis for comparisons with international data. The World Health Organisation questionnaire was used, together with a multi-stage stratified cluster sampling technique; 1,700 subjects aged 15 years and above were randomly selected. A total of 1,486 individuals (87.4%) from among the populations of Al-Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
3
10
0
1
Order By: Relevance
“…Its prevalence rate in this study among Saudi male secondary school students was 22.6%. This figure is comparable with what has been reported in other Saudi Arabian studies (19%-29%), [42][43][44] in the United Arab Emirates (19%), [45] and in Yemen (19.6%). [46] t is much higher than what has been reported in Oman (4.5%).…”
Section: Discussionsupporting
confidence: 91%
“…Its prevalence rate in this study among Saudi male secondary school students was 22.6%. This figure is comparable with what has been reported in other Saudi Arabian studies (19%-29%), [42][43][44] in the United Arab Emirates (19%), [45] and in Yemen (19.6%). [46] t is much higher than what has been reported in Oman (4.5%).…”
Section: Discussionsupporting
confidence: 91%
“…Further, most studies ignore differences in ‘taking a puff’ versus ‘smoking a cigarette’ (see LaPrelle et al . 1992 for an exception) and few studies examine quitting (see Bener & Al‐Ketbi 1999 for an exception), so variation in smoking behavior at the initiation and cessation ends of the spectrum is rarely assessed. In short, we suspect that community influences affect current smoking, but we have little idea how they affect initiation, change in frequency/amount, stabilization or quitting.…”
Section: The Applicability Of Community Ecological Models To Youth Smmentioning
confidence: 99%
“…Adolescent (14–18 years) tobacco use varies from 23% to 58% (Al‐faris, 1995; Saeed et al., 1996; Kulwicki & Kepler, 2001). Additional studies revealed a 34.4% smoking rate in Kuwaiti males (15–20 years) (Moody, Memon, Sugathan, El‐gerges, & Al‐Bustan, 1998); 39.9% in 18‐ to 22‐year‐old Iraqi college students (Jamil, Mukhlis, & Saadon, 1989); and 30.3% among 15‐ to 19‐year‐olds in the United Arab Emirates (Bener & Al‐Ketbi, 1999). In three regions of Saudi Arabia, the overall prevalence of current smoking for individuals 15 years and older was 21.1% for males and 0.9% for females (Jarallah, al‐Rubeaan, al‐Nuaim, al‐Ruhaily, & Kalantan, 2000).…”
mentioning
confidence: 99%